Storm Gloria: Sea State Evolution Based on in situ Measurements and Modeled Data and Its Impact on Extreme Values - de Alfonso, Marta; Lin-Ye, Jue; García-Valdecasas, José M.; Pérez-Rubio, Susana; Luna, M. Yolanda; Santos-Muñoz, Daniel; Ruiz, M. Isabel; Pérez-Gómez, Begoña; Álvarez-Fanjul, Enrique (Frontiers in Marine Science, 2021)
Storm Gloria, generated January 17th, 2020 in the Eastern North Atlantic, crossed the Iberian Peninsula and impacted the Western Mediterranean during the following days. The event produced relevant damages on the coast and infrastructures at the Catalan-Balearic Sea due to the effect of extraordinary wind and wave fields, concurrent with anomalous high sea-level values. Puertos del Estado (the Spanish holding of harbors) has developed and operates a complex monitoring and forecasting system (PORTUS System), in collaboration with the Spanish Met Office (AEMET). The present work shows how Gloria was correctly forecasted by this system, alerts were properly issued (with special focus to the ports), and the buoys were able to monitor the sea state conditions during the event, measuring several new records of significant wave height and exceptional high mean wave periods. The paper describes in detail the dynamic evolution of the atmospheric conditions and the sea state during the storm by means of the study of both in-situ and modelled PORTUS data, in combination with the AEMET weather forecast system results. The analysis also serves to place this storm in a historical context, showing the exceptional nature of the event, and to identify the specific reasons why its impact was particularly severe. The work also demonstrates the relevance of the PORTUS System to warn in advance the main Spanish Ports in order to prevent accidents that could result in fatal casualties. To do so, the wave forecast warnings performance is analyzed, making special focus on the skill score for the different horizons. Finally, it is demonstrated how a storm of this nature results in the need of changes on the extreme wave analysis for the area, which impacts all sorts of design activities at the coastline. The paper studies both how this storm fits on previous existing extreme analysis and how these should be modified in the light of this particular single event. This work is the first of a series of papers to be published on this issue, analyzing in detail other aspects of the event including evolution of sea level, description of coastal damages and others.